Formulation Policy of Weekend Detention In Indonesia Criminal Law Reform - hidayat, muhammad thaufik; Widyawati, Anis (IJCLS (Indonesian Journal of Criminal Law Studies), 2020)
The purpose of this study is to explain and describe how the formulation policy of weekend detention in Indonesia's positive law and how the formulation policy of weekend detention in the Indonesian criminal law reform in the futureÂ  (ius constituendum). This research uses normative juridical method of research which is legal research conducted by examining the library material in the form of secondary data such as law or library material as well as other documents that support and data retrieval technique used is library research techniques and analysis of data used is interactive analysis model. The results showed that (1) criminal formulation policy the weekend detention in Indonesia's positive law of the arrangement in the correctional Institution is not regulated about the policy of weekend detention. However, in Indonesian positive law formulation has an assimilation program which is one of the programs in the actual criminal implementation almost resembles a weekend detention system. (2) The policy formulation of the weekend detention in the renewal of Indonesian criminal law (penal policy) can be done by the study of the law comparative countries such as France, Portugal, Vanuatu, Queensland and New South Wales that have implemented a relatively advanced prison system that is the weekend detention. The formulation of weekend detention that is expected to be valid in Indonesia in the future is to develop it firmly in the draft Penal code and paste it in article 65 the Draft Penal code or if the government is about to arrange codification in the law of criminal implementation, the weekend detention is entered in one of the types of criminal sanctions.